PENGEMBANGAN PROGRAM EKSTRAKURIKULER PANAHAN DALAM MEMBENTUK KARAKTER SISWA MI PLUS NURUL HUDA CIJUREY - Sugiarti, Sri; Mutmainah, Naeli; Ahyani, Hisam (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
The archery extracurricular program at MI Plus Nurul Huda Cijurey aims to shape students' character by integrating the principles of Islamic education. Archery activities not only teach physical skills, but also instill the values ​​of discipline, calmness, precision, and patience. This study uses the research and development (R&D) method to design and develop an effective extracurricular program in strengthening students' character and spirituality. The results of the study showed that the archery program increased concentration, togetherness, self-confidence, and the ability to be patient. This program also supports the formation of noble morals and strengthens the attitude of tawakal, which is in line with the principles of Islamic education. Overall, this program has a positive impact on the physical, mental, and spiritual aspects of students.